Green Lean Practices towards Increasing Operation Value of Manufacturing Company - Ahmad, Ahmad Nur Aizat; Ahmad, Md Fauzi; Abdul Hamid, Norhadilah; Ngadiman, Yunos; Pakir, Mohamed Ismail; Nawanir, Gusman; Bakri, Adnan; Abdul Rahim, Mustaqqim (International Journal of Integrated Engineering, 2020)
Nowadays, manufacturing industries are rapidly developing. However the constraints faced by today's producers are how to produce their products quickly through low costs while at the same time, the reduction of waste disposal in the environment. The high waste of time in the manufacturing industry is often attributed to the wastage that occurred in the company’s operations. Lean manufacturing is linked for improving the standard working. It is one of the production strategies that drive the industry towards a more efficient production of goods and services. Meanwhile, green manufacturing has been adopted as a requirement to achieve a minimal negative impact on the environment. The green lean is a concept to make sure system more efficient, reduce unwanted product releases and minimize the environmental impact. So, the main objective of this research is to reduce cycle time in manufacturing company by adopting green lean elements. This research focuses on furniture manufacturing and conducted a structural interview question, observation and time study method. To refine those time operation problems, the company had implemented the new green lean practices into the operation department. The results after implement these methods totally show an improved progress. The paper would help the manufacturer to organize and improve their company performance. In conclusion, this research is about to identify and reduce the time waste to improve the operation value of the manufacturing company while at the same time it would reduce the environmental impact in future.